Subacute combined degeneration of the cord, dementia and parkinsonism due to an inborn error of folate metabolism. Issue 8 (August 1986) - Clayton, P T; Smith, I; Harding, B; Hyland, K; Leonard, J V; Leeming, R J
Abstract : A 2-year-old girl with 5, 10-methylenetetrahydrofolate reductase deficiency developed subacute combined degeneration of the cord and a leuco-encephalopathy which was confirmed at necropsy. Total folate concentrations in serum, red cells and CSF were markedly reduced whereas vitamin B12 concentrations were normal. In addition the patient had Parkinsonism and reduced concentrations of homovanillic acid, 5-hydroxyindoleacetic acid and total biopterins in cerebrospinal fluid. Folic acid administration was accompanied by fits and acute deterioration in the movement disorder. At necropsy the basal ganglia showed no detectable abnormality.